Building trust and transparency? Challenges of the opt-out system and the secondary use of health data in England. (June 2019) - Meszaros, Janos; Ho, Chih-hsing
After the failure of the care.data programme, a revised opt-out system has been introduced for British citizens to protect their health data from 2018. However, there are several exemptions from the previous and the revised opt-out systems, some of which are overly broad. For instance, the opt-outs may be completely ignored in the case of 'anonymised' data. The data protection terminology in the United Kingdom is slightly different from that in the European Union, and the key issue is that the terms are not used consistently, even in the most important documents and guidelines. This situation may lead to a weak opt-out system with transparency issues, which might erode public trust and lead to a repeat of the care.data failure. Furthermore, the United Kingdom intends to comply with the General Data Protection Regulation after Brexit, thus these differences may cause compatibility issues in the future.